PBL-Based Student Worksheet to Improve Critical Thinking Ability in Science Learning in Elementary Schools - Pramudiyanti, Pramudiyanti; Pratiwi, Wulan Octi; Armansyah, Armansyah; Rohman, Fatkhur; Putri, Intan Yulia; Ariani, Devi (Indonesian Journal of Science and Mathematics Education, 2023)
This study aims to create a student worksheet based on the Problem-based Learning (PBL) model in science learning, test its feasibility, and identify student and teacher responses to the implementation of the student worksheet. The instruments were validation sheets and student and teacher response questionnaires. The research data were descriptively and qualitatively analyzed based on the criteria score. Material expert validation obtained an average of 0.8409 with "high" criteria. An average of 0.8036 with "high" criteria was obtained for language expert validation. Media expert validation obtained an average of 0.7522 with "moderately high" criteria. According to the findings of the field trial, the average response of teachers was 86% with the criteria "excellent," and the average response of students was 85% with the criteria "excellent and highly suitable." Furthermore, the n-gain value obtained was 0.7 in the "moderate" category. As a result, the developed student worksheet can be used to improve students' critical thinking skills. Thus, teachers are advised to create student worksheets based on other materials.